2011
DOI: 10.1016/j.jpurol.2011.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and fate of the remnant moiety following laparoscopic heminephrectomy for duplex kidney: A multicenter review

Abstract: LHN for duplex kidney produces satisfactory outcomes in the pediatric population. With a median follow up of 4.5 years, we demonstrate a non-functioning renal moiety rate of 5%. We did not identify any clinical predictors of this outcome in our series, although upper pole heminephrectomy, patient age, and postoperative complications may be contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 16 publications
0
14
0
7
Order By: Relevance
“…These being: urinoma, urinary tract infection and/or vascular compromise on the remaining moiety. [3,4] The case we report shows a further complication of ischemic damage to the remaining ureter after heminephroureterectomy.…”
Section: Abstract: Complication Heminephroureterectomy Ischemia Inmentioning
confidence: 76%
See 1 more Smart Citation
“…These being: urinoma, urinary tract infection and/or vascular compromise on the remaining moiety. [3,4] The case we report shows a further complication of ischemic damage to the remaining ureter after heminephroureterectomy.…”
Section: Abstract: Complication Heminephroureterectomy Ischemia Inmentioning
confidence: 76%
“…[1,2] The procedure has only few reported complications: of which include an urinoma, urinary tract infection and/ or vascular compromise in the moiety that remains. [3,4] We report a further complication of possible vascular ischemic injury to the normal remaining upper pole ureter after lower pole heminephroureterectomy. As far as the authors are aware, it has not been reported in the English literature.…”
Section: Abstract: Complication Heminephroureterectomy Ischemia Inmentioning
confidence: 90%
“…Segmental MCDK was not associated with complete loss of function of the involved pole, and resection carried with it the risk of damaging the other normal segment. 20,21 The principle of management of segmental MCDK has not been established due to the limited number of reports. To our knowledge, only 37 pediatric cases and 2 adult cases of segmental MCDK have been reported worldwide.…”
Section: Complicationsmentioning
confidence: 99%
“…Post-operatively, most patients recover well, and the length of stay in hospital is modest. Rarely, patients develop post-operative urinoma, or a decline in function of the remaining moiety which may necessitate further intervention [13]. …”
Section: Introductionmentioning
confidence: 99%